Sustaining seas oceanic space and the politics of care - Probyn, Elspeth, 1958-; Johnston, Kate, 1979-; Lee, Nancy, 1986- (Rowman & Littlefield International Ltd., 2020)
"Why read Sustaining Seas? It is as simple as this: the seas sustain all life. This edited book emerges from conversations across several disciplines, and including practitioners of different specialities (artists, writers, planners, policy makers) about how to sustain the seas, as they sustain us"--